Strategi Rumah Data Kependudukan Terintegrasi dengan “BIONIK SYSTEM” di Kota Bogor - Sujatmiko Baliarto (Neolectura, 2022)
The purpose of this paper is to discuss and examine the Strategy of the Integrated Population Data House with the